2024
DOI: 10.1121/10.0025136
|View full text |Cite
|
Sign up to set email alerts
|

Predicting early auditory evoked potentials using a computational model of auditory-nerve processing

Miguel Temboury-Gutierrez,
Gerard Encina-Llamas,
Torsten Dau

Abstract: Non-invasive electrophysiological measures, such as auditory evoked potentials (AEPs), play a crucial role in diagnosing auditory pathology. However, the relationship between AEP morphology and cochlear degeneration remains complex and not well understood. Dau [J. Acoust. Soc. Am. 113, 936–950 (2003)] proposed a computational framework for modeling AEPs that utilized a nonlinear auditory-nerve (AN) model followed by a linear unitary response function. While the model captured some important features of the mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
1
1
0
Order By: Relevance
“…However, the model is not fully accurate and did not predict the remaining talker differences after matching f0 or the latency changes in click ABRs with increasing rate. These limitations of the computational model are consistent with other studies that also found appropriate predictions of amplitude but not latency changes with stimulus level changes in click ABRs (e.g., Dau, 2003;Temboury-Gutierrez et al, 2024). They suggested that the limitations could be due to an oversimplification of neural processing in the brainstem model, which assumes constant delays through the brainstem that may not be accurate for broadband or complex stimuli.…”
Section: Modeled Abrs Reasonably Approximate Stimulus-f0 Effects But ...supporting
confidence: 81%
See 1 more Smart Citation
“…However, the model is not fully accurate and did not predict the remaining talker differences after matching f0 or the latency changes in click ABRs with increasing rate. These limitations of the computational model are consistent with other studies that also found appropriate predictions of amplitude but not latency changes with stimulus level changes in click ABRs (e.g., Dau, 2003;Temboury-Gutierrez et al, 2024). They suggested that the limitations could be due to an oversimplification of neural processing in the brainstem model, which assumes constant delays through the brainstem that may not be accurate for broadband or complex stimuli.…”
Section: Modeled Abrs Reasonably Approximate Stimulus-f0 Effects But ...supporting
confidence: 81%
“…Computational modeling has been previously used to simulate ABRs and explore stimulus differences (e.g., Dau, 2003;Stoll and Maddox, 2023;Temboury-Gutierrez et al, 2024). Average ABRs (areas show ± SE) measured in previous work (left, n = 11) and the current study (right, n = 15) are larger and earlier for male-than female-narrated speech.…”
Section: Introductionmentioning
confidence: 57%